Mechanical Properties of Asymmetric Woven Bamboo Structure from Bamboo Strips - Ekkarin Phongphinittana; Navapon Klangtup; Petch Jearanaisilawong (Fibers, 2025)
The study evaluates the mechanical properties of a woven bamboo structure made from bamboo strips using an analytical relation and finite element simulation. The bamboo studied is a recently discovered species, Bambusa Nghiana, characterized by long internodes. Bamboo strips have lower strength at the node junctions, a feature that can be advantageous for this species due to its extended internode length. Plain weave bamboo structures were handwoven from thin, rectangular bamboo strips cut from the bamboo culm along the radial direction. The high bending rigidity of the bamboo strips resulted in an asymmetric woven structure with curved warp strips and straight weft strips. The stiffness of the woven structure was correlated with the stiffness of the bamboo strips and the weave geometry. The in-plane shear resistance of the woven structure was significantly lower than its axial stiffness due to the asymmetric weaving. These in-plane properties were validated using finite element simulation through a user subroutine incorporating the woven structure and the Hashin damage criteria. The prediction of the puncture simulation showed good agreement with the corresponding experiment. These results confirm the proposed analytical relation between the mechanical properties of individual bamboo strips and those of the woven structure.